2015
DOI: 10.1038/mt.2015.178
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Crosslinking: A General Method to Trigger Internalization and Lysosomal Targeting of Therapeutic Receptor:Ligand Complexes

Abstract: A major unmet clinical need is a universal method for subcellular targeting of bioactive molecules to lysosomes. Delivery to this organelle enables either degradation of oncogenic receptors that are overexpressed in cancers, or release of prodrugs from antibody–drug conjugates. Here, we describe a general method that uses receptor crosslinking to trigger endocytosis and subsequently redirect trafficking of receptor:cargo complexes from their expected route, to lysosomes. By incubation of plasma membrane recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
102
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 67 publications
6
102
0
Order By: Relevance
“…The siRNA oligonucleotide sequence 5′-GAGCAUGUGCACGCUGGCCA-3′ targeting μ2-2 subunit of AP-2 is highly effective to achieve nearly complete depletion of AP-2 with two cycles of transfection, as reported by Motley et al 44 and confirmed by others 45, 46 . The siRNA treatment was performed following the established protocol.…”
Section: Resultsmentioning
confidence: 57%
“…The siRNA oligonucleotide sequence 5′-GAGCAUGUGCACGCUGGCCA-3′ targeting μ2-2 subunit of AP-2 is highly effective to achieve nearly complete depletion of AP-2 with two cycles of transfection, as reported by Motley et al 44 and confirmed by others 45, 46 . The siRNA treatment was performed following the established protocol.…”
Section: Resultsmentioning
confidence: 57%
“…It should be noted that Moody et al demonstrated that the recycling rate of transferrin and Her2 receptors was altered and that the cargo was redirected to the lysosome when the receptors were crosslinked with biotinylated cargo and the addition of streptavidin. (44) Therefore, it seems possible that multivalent particles, such as the folate decorated micelleplexes described here, which can bind and occupy multiple receptors on the cell surface, can alter the receptor's natural endocytic pathway to enhance the delivery of therapeutic agents to the lysosome. This agrees with other multivalent FRα targeting studies suggesting that multivalent particles follow a lysosomal pathway to the cytosol.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, specific mean to inhibit clathrin-mediated endocytosis was carried out by siRNA knockdown of AP-2 µ2 subunit in A549 cells. The siRNA oligonucleotide sequence 5′-GAGCAUGUGCACGCUGGCCA-3′ targeting μ2-2 subunit of AP-2 is highly effective to achieve nearly complete depletion of AP-2 with two cycles of transfection, as reported by Motley et al 44 and confirmed by others 45,46 . The siRNA treatment was performed following the established protocol.…”
Section: Resultsmentioning
confidence: 58%